Enhancing farmers' income: who to target and how? - Birthal, Pratap S.; Negi, Digvijay S.; Roy, Devesh (National Institute of Agricultural Economics and Policy Research, 2017)
Recognizing that the growing distress among farming community may disturb socio-political equilibrium and affect nation’s food security the government of India in its budget of 2016-17 has set a policy target of doubling farmers’ income by 2022. To achieve this, the government has announced a number of innovative measures that include improving farmers’ access to institutions (i.e. credit, insurance, information, common markets), development of infrastructure (i.e. irrigation, electricity and roads), restoring soil health, improving efficiency of agricultural markets, expanding dairy processing facilities and enhancing farmers’ capacity to diversify into nonfarm activities.